A Nonlinear Strength Criterion for Frozen Sulfate Saline Silty Clay with Different Salt Contents - Yanhu Zhao; Yuanming Lai; Jing Zhang; Chong Wang (Advances in Materials Science and Engineering)
It has been proven that the mechanical properties of frozen saline soils are different from frozen soils and unfrozen saline soils. In this paper, in order to study the effects of the salt contents on the strength characteristics of frozen soils, a series of conventional triaxial compression tests are carried out for frozen saline silty clay with Na2SO4 contents 0.0, 0.5, 1.5, and 2.5% under confining pressures from 0 MPa to 18 MPa at −6°C, respectively. The experimental results show that the strength of frozen saline silty clay presents obvious nonlinearity, the strength of frozen saline silty clay increases with increasing confining pressures at first, but with a further increase in confining pressures, the strength decreases because of pressure melting and crushing phenomena under high confining pressures, and salt contents have an important influence on strength of frozen saline silty clay. A strength criterion is proposed on the basis of the experimental results. The strength criterion could well reflect the nonlinear strength characteristic of frozen saline silty clay and the influence of salt contents on frozen saline silty clay.